Towards Quality Teacher Education in India: NCTE Regulatory Mechanism, Norms and Initiatives - Sahay, Vikram (JOURNAL OF INDIAN EDUCATION, 2026)
Teacher education plays a crucial role in shaping the quality of education at all societal levels. It equips teachers with the knowledge, skills and professional values needed to foster student learning and growth. Quality teacher education ensures that educators are not only subject matter experts but also skilled in pedagogy — the art and science of teaching. This includes understanding diverse learning needs, creating inclusive classrooms and applying modern instructional techniques to engage students. A strong foundation in teacher education also helps teachers manage classroom dynamics, address behavioural challenges and create a positive learning environment. In turn, this enhances student success, builds confidence and prepares young minds for future challenges. Teachers with intense training can inspire curiosity, encourage critical thinking and nurture creativity. Fostering the continuous professional development of teachers is another crucial function of teacher education. As societies evolve and new technologies emerge over time, well-trained teachers can also adapt by updating their teaching strategies and remaining lifelong learners themselves. Ultimately, the importance of teacher education cannot be overstated, as it directly impacts the quality of education and by extension, the future of individuals and communities in a nation